79 BALLOON DILATION FOR GASTROJEJUNAL STENOSIS IN GASTRIC BYPASS SURGERY. (1st January 2006) - Whitt, K.; Madan, A.; Bessoff, J.; Tombazzi, C.
Abstract : Background and Aims: Gastrojejunal stenosis is a common complication of Roux-en-Y gastric bypass surgery. It occurs in around 15% of gastric bypass surgeries. We have an active obesity surgery program at our institution. Here we report our experience over a period of approximately 2 years in the endoscopic management of gastric outlet obstruction in bariatric surgery patients. Methods: We retrospectively analyzed all endoscopic dilatations performed by a member of our gastroenterology division on bariatric surgery patients. Data were compiled from an endoscopy database and review of clinic charts. Results: Ten bariatric surgery patients were managed endoscopically for intolerance to liquids between January 2004 and August 2005. In all except one case, through-the-scope (TTS) balloon dilators were used. Three of 10 patients were male. Two of the patients had undergone open Roux-en-Y gastric bypass in the 1990s and underwent their first dilation procedure at at 145 months and 83 months postoperatively. Full weight loss data are unavailable on these patients. The rest underwent surgery between 2003 and 2005; two surgical attendings specializing in laparoscopic obesity surgery performed all of these operations. Only one patient had vertical banded gastroplasty while the rest had laparoscopic gastric bypass surgery. Patients presented at a mean of 188 days after surgery (range 64 to 468 days) and required a mean of 2.9 (range 1-5) endoscopic dilations. During sessions, endoscopists most commonly dilated to 12 mm. Maximal dilation was to 18 mm. There were no immediate complications to balloon dilation, and obstructive symptoms generally resolved. The patient with a vertical banded gastroplasty later required operative management for gastric outlet obstruction. No other patients required operative intervention for treatment of anastamotic stricture. Mean BMI preoperatively in the group was 51.8 (range 45.3 to 59.3), and mean BMI decrease was 225.5 (range 15.2 to 32.6). This degree of weight loss is felt to be slightly superior to that typically seen in our bariatric surgery patients. Conclusions: Endoscopic TTS balloon dilation is a safe and effective treatment for anastomotic stricture in gastric bypass patients. Endoscopic therapy does not seem to be as beneficial for patients who have had vertical banded gastroplasty. The development of gastrojejunal stenosis may positively impact weight loss. Avoidance of overdilation necessitates more endoscopic procedures to restore tolerance to solids but may contribute to successful weight reduction.